Anopheles gambiae Actively Metabolizes Uric Acid Following Plasmodium Infection to Limit Malaria Parasite Survival - Kwon, Hyeogsun; Smith, Ryan (Frontiers in Physiology, 2022)
Characterizing the physiological changes that accompany malaria parasite infection of the mosquito host is crucial to our understanding of vectorial capacity in Anopheles mosquitoes, yet has not fully been explored. In this study, we examine the role of uric acid metabolism in the mosquito, Anopheles gambiae, following malaria parasite infection. We demonstrate that levels of uric acid are significantly decreased in the excreta and the mosquito at 24h and 48h post-Plasmodium infection when compared to controls fed on naïve mouse blood. When we examine the expression of well-known enzymes responsible for uric acid metabolism, we see a significant increase in both urate oxidase (UO) and allatoicase (ALLC) expression following Plasmodium infection. Targeting the essential first step in uric acid metabolism by silencing UO resulted in elevated levels of uric acid, enhancing malaria parasite survival. With implications from other insect systems that bacteria can modulate UO expression, we examined the possibility that the mosquito microbiota and its expansion following blood-feeding may contribute to increased UO levels. However, there was no difference in uric acid metabolism between septic and aseptic mosquitoes, indicating that the mosquito microbiome is not associated with the manipulation of UO expression. Together, our study provides new evidence that Plasmodium infection causes the mosquito host to actively metabolize uric acid by increasing UO expression to limit Plasmodium oocyst survival, suggesting that nitrogen metabolism is an essential pathway in defining mosquito vector competence.